Implementasi Network Intrusion Detection System (NIDS) Dalam Sistem Keamanan Open Cloud Computing - Muqorobin Muqorobin; Zul Hisyam; Moch Mashuri; Hanafi Hanafi; Yudhi Setiyantara (Sekolah Tinggi Maritim Yogyakarta, 2019)
Security is the most important part of computer network technology systems. Among the technologies that utilize networks are cloud computing. One cloud computing provider such as eucalyptus uses a firewall for system security. The use of a firewall on the system cannot monitor and analyze traffic that is inside the cloud server and does not give a warning when an attack occurs. The purpose of this study is that researchers will implement a network intrusion detection system (NIDS) in cloud computing and mirroring traffic on switches. Intrusion detection system (IDS) is a security technology that can analyze network traffic and detect traffic if an attack is indicated. NIDS are placed hosted differently from cloud computing servers. With the switch mirroring traffic method, traffic will be directed to NIDS so that NIDS can record all network traffic originating from outside the cloud server or traffic between virtual machines within the cloud server. The test results of attacks with 2 scenarios, namely attacks from outside and from within the cloud system, then NIDS is able to provide an alert response to traffic attacks.